Patterns and trends of pediatric and young adult computed tomography use in Brazil: 2008-2014 (Brazilian Journal of Radiation Sciences, 2020)
ABSTRACT Computed tomography (CT) is an indispensable imaging technique, but radiation exposure from CT scans is of concern mainly due to the potential risk of developing cancer, mainly in children. Our group recently showed that CT use has greatly increased among outpatients using the Brazilian public health system (SUS) between 2001 and 2011. Further, CT examinations among patients younger than 20 years of age represented around 13.4% of all CT examinations in SUS between 2008 and 2011. In comparison, these examinations represented around 8% of the overall number of CT scans in a private hospital in Rio de Janeiro between 2005 and 2015, In this paper we extended the evaluation of pediatric and young adult CT use in Brazil to 25 private CT services in 8 Brazilian cities for the period 2008-2014. Data from SUS was updated to this period. Information about CT use in SUS was obtained from an online database. Data on the privately funded setting was retrieved from the Radiological Information Systems (RIS) of each CT service. Patients younger than 20 years of age underwent around 8.9% of the CT procedures in the private setting, while in SUS this proportion was around 12.7% in the same period. Pediatric and young adult CT greatly increased in both healthcare systems, but annual growth rates were less pronounced in the private than in the public healthcare system. One third of the patients in the private setting had more than one CT examination over the period investigated.